Struktur Dan Fungsi Sosial Cerita Rakyat Legenda Patung Sigale-Gale Di Huta Siallagan Kecamatan Simanindo Kabupaten Samosir Provinsi Sumatera Utara - Susi Margareth Saing; Hasanuddin WS (Persona: Kajian Bahasa dan Sastra, 2023)
This page tries to clarify and outline: (1) the composition of the folklore around the Sigale-gale Statue, located in the Simanindo District of the Samosir Regency of North Sumatra Province; and (2) the significance of the statue. (2) The social significance of the Sigale-gale Statue's folklore legend in the Simanindo District of Samosir Regency, North Sumatra Province. A descriptive methodology is being used in this qualitative investigation. The Sigale-gale Statue's folklore is the focus of this study, which is located in Huta Siallagan, Simanindo District, Samosir Regency, North Sumatra Province. Through observation, interviews, and recorded interviews, information can be gathered from informants. The gathered data underwent multiple levels of analysis. (1) describing the data; (2) classifying or analyzing the data; (3) discussing the analysis of the findings of the classification; and (4) reports. The findings of this study suggest that: 1) The Sigale-gale Statue folklore legend in the Simanindo District, Samosir Regency, North Sumatra Province, has the following elements: style, characterizations, storyline, place, topic, and message. 2) The Sigale-gale Statue in Simanindo District, Samosir Regency, North Sumatra Province, serves three societal purposes: (a) disseminating, (b) educating, and (c) entertaining.